2011
DOI: 10.1007/s11655-011-0800-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical observation on the acupuncture treatment in patients with urinary retention after radical hysterectomy

Abstract: Combination of acupuncture: modalities was better than acupoint injection for the recovery of bladder function in urinary retention after radical hysterectomy. It would shorten the course of treatment and get a better recovery, decrease urinary retention cases of refractoriness, and extending the treatment could raise the healing rate of urinary retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 5 publications
0
36
0
Order By: Relevance
“…The age of patients among studies ranged from 19 to 75, 23 studies we included, but only 3 studies [ 39 – 41 ] described the indicator of body mass index (BMI). 12 studies [ 39 , 42 – 52 ] had a course of treatment less than or equal to one week, 8 studies [ 40 , 41 , 53 – 58 ] owned a treatment course over one week, and 3 studies [ 59 – 61 ] did not show the treating time. 10 studies [ 39 – 41 , 45 , 46 , 48 , 49 , 55 – 57 ] were performed on hysterectomy, 8 [ 42 – 44 , 47 , 51 , 59 – 61 ] were performed on anorectal surgery, 2 [ 52 , 58 ] were performed on orthopedic surgery, 1 [ 53 ] was performed on prostate surgery, 1 [ 50 ] was performed on spinal anaesthesia, and 1 study [ 54 ] did not indicate the type of surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The age of patients among studies ranged from 19 to 75, 23 studies we included, but only 3 studies [ 39 – 41 ] described the indicator of body mass index (BMI). 12 studies [ 39 , 42 – 52 ] had a course of treatment less than or equal to one week, 8 studies [ 40 , 41 , 53 – 58 ] owned a treatment course over one week, and 3 studies [ 59 – 61 ] did not show the treating time. 10 studies [ 39 – 41 , 45 , 46 , 48 , 49 , 55 – 57 ] were performed on hysterectomy, 8 [ 42 – 44 , 47 , 51 , 59 – 61 ] were performed on anorectal surgery, 2 [ 52 , 58 ] were performed on orthopedic surgery, 1 [ 53 ] was performed on prostate surgery, 1 [ 50 ] was performed on spinal anaesthesia, and 1 study [ 54 ] did not indicate the type of surgery.…”
Section: Resultsmentioning
confidence: 99%
“…10 studies [ 39 – 41 , 45 , 46 , 48 , 49 , 55 – 57 ] were performed on hysterectomy, 8 [ 42 – 44 , 47 , 51 , 59 – 61 ] were performed on anorectal surgery, 2 [ 52 , 58 ] were performed on orthopedic surgery, 1 [ 53 ] was performed on prostate surgery, 1 [ 50 ] was performed on spinal anaesthesia, and 1 study [ 54 ] did not indicate the type of surgery. All of the included studies used EA with or without other treatments as intervening measure, 8 of these studies [ 39 , 41 , 43 , 45 , 54 , 55 , 57 , 58 ] compared EA with usual care and physiotherapy, and 10 studies [ 40 , 42 , 46 – 49 , 51 , 53 , 56 , 59 ] compared EA with medication. 5 studies [ 44 , 50 , 52 , 60 , 61 ] set EA as intervening measure while there was no intervention in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Acupuncture has positive effects on nerve regeneration process and provides an alternative treatment on nerve-injured patients [20, 21]. For the patients after RH, acupuncture may help the impaired nerve restoration and reconstruction which are essential for preventing bladder dysfunction [11, 22]. Another possible mechanism of acupuncture effect for bladder dysfunction lies in the regulation and balance of neurotransmitter, such as catecholamines.…”
Section: Discussionmentioning
confidence: 99%
“…But few literatures are randomized controlled trial and published in English. In our previous study, acupuncture showed some effects in treating urinary retention after RH [11]. Refractory cases of urinary retention still occurred when we started acupuncture treatment two weeks after RH procedure.…”
Section: Introductionmentioning
confidence: 98%
“…But a recent randomized trail showed that this bladder training did not reduce the rate of UR or re-admission for bladder catheterization [8]. Some Chinese doctors use acupuncture to treat UR after radical hysterectomy with potential efficacy [9], but more studies are needed to prove its effects due to limited sample size and poor study design, moreover, acupuncture is difficult to apply, in general, due to the specialized technique. For those with chronic UR, clean intermittent catheterization or even suprapubic cystostomy is needed which are associated with frequent urinary tract infection [10].…”
Section: Introductionmentioning
confidence: 99%